Uncontrolled, Open-Label Pre-Dinner Administration of Elobixibat in Japanese Adults with Chronic Constipation: A Retrospective Chart Review - Takeo Odaka, MD, PhD; Kazunari Tominaga, MD, PhD (Elsevier, 2020)
Background: Elobixibat has been approved as a new therapeutic drug for chronic constipation. Only the pharmacological efficacy and safety profile of pre-breakfast administration of elobixibat had been previously demonstrated. Objective: We evaluated the efficacy and safety profile of pre-dinner administration of elobixibat in patients with functional constipation in a retrospective observational study. Methods: Patients aged 20 years or older diagnosed with functional constipation by the Rome IV criteria from June 1, 2018, to January 17, 2019. The evaluation time points were at the start and 1, 2, 4, and 8 weeks after treatment. The primary end point was frequency of spontaneous bowel movements per week. The secondary end points were changes in Bristol Stool Form Scale score, onset time required for spontaneous defecation after administration, percent of patients with spontaneous defecation within 24 hours and 48 hours after the first administration, improvement of abdominal pain or abdominal bloating evaluated by a visual analog scale, and total score and each subscore of the Japanese-Translated Version of Patient Assessment of Constipation Quality of Life Questionnaire. Results: Pre-dinner administration of elobixibat was associated with significantly increased frequency of spontaneous bowel movements and improved Bristol Stool Form Scale score at 1, 2, 4, and 8 weeks after treatment. The mean onset time until spontaneous defecation after treatment was 4 to 5 hours, which was earlier than that by conventional constipation treatment drugs and almost constant within an individual during the treatment period. Spontaneous defecation was achieved by 85.4% within 24 hours and 90.2% within 48 hours after the first administration. Elobixibat also improved patients' quality of life, which was evaluated by the Japanese-Translated Version of Patient Assessment of Constipation Quality of Life Questionnaire without adverse events. Conclusions: Pre-dinner administration of elobixibat improved constipation, abdominal pain and bloating, and patient quality of life by management of fixed defecation. (Curr Ther Res Clin Exp. 2020; 81:XXX-XXX)